A single-stage dual-output tri-mode AC-DC regulator for inductively powered application - Low, Qiong Wei (2021)
This paper presents a one-stage AC-DC voltage regulator with dual-output for inductively powered applications. In order to maximize the circuit performances, more than one independent regulated output voltage is often required to cater for different sub-modules in a system. The typical two-stage implementation which consists of a rectifier and a multiple-output DC-DC converter limits the overall power conversion efficiency of the receiver. A new architecture which is able to rectify and regulate two or more output voltages simultaneously in a single-stage is proposed and thereby improving the overall power conversion efficiency substantially. In addition, an energy-efficient control scheme is adopted to control the multiple switches in the architecture. Since no inductor is required in the proposed one-stage conversion structure, the cross-regulation problem that used to exist in a multiple-output switching converter has been eliminated. Apart from this, it is easier to be integrated with a system-on-chip (SoC) due to its minimized footprint. The tri-mode dual-output design was fabricated in standard 0.18μm CMOS process. It delivers a maximum output power of 114mW. The measured peak power conversion efficiency is 91.7% at dual regulated output voltages of 1.8V and 2V.